Determination of the chemical profile extracts obtained from Kalanchoe pinnata (Lam.) Pers native of municipality Tabatinga-AM (Research, Society and Development, 2022)
Kalanchoe pinnata formerly known as Bryophyllum pinnatum , is a herbaceous species native to tropical regions such as Africa. In Brazil, it was successfully introduced and propagated, being commonly used in communities far from large capitals. The juice of the leaves is usually used in the treatment of inflammatory diseases, gastric ulcers, burns, diarrhea , vomiting, insect bites and body aches. In the literature, compounds such as anthocyanins and flavonoids are reported that have different biological activities such as antimicrobial, antioxidant, cytotoxic, antitumor, antiparasitic, antiallergic and hepatoprotective . Based on this information and considering that there are few studies on the chemical compounds of K. pinnata in Amazonas , especially in regions farther from the capital, such as in the municipality of Tabatinga. The present work aimed to determine the chemical profile of the fractions of the crude extract of K. pinnata native to the municipality of Tabatinga - AM. For this, plant material was collected from a local producer in the municipality of Tabatinga. Then the leaves were subjected to an extraction by infusion. Soon after, the crude extract obtained was fractionated with hexane, chloroform and ethyl acetate. The resulting fractions were analyzed by High Performance Liquid Chromatography (HPLC) at wavelength λ=254 nm and, using the information available in the literature, it was possible to establish a relationship between the compound quercetin 3- O -α-L- arabinopyranosyl - (1→2)-α-L- rhamnopyranoside , as responsible for the chromatographic peaks observed in the hexane, chloroform, and ethyl acetate fractions. Thus, the present study will serve as a basis for future work on the characterization of chemical compounds present in K. pinnata from the municipality of Tabatinga.